Konsep Bullying Di Sekolah Dasar - Wibawa, Andi (Universitas Sebelas Maret, 2022)
This article discusses the concept of bullying in the elementary school environment, focusing on the phenomenon of violence and intimidation experienced by students. By using a multidimensional approach, this research explores the roots of the problem, the dynamics of interaction between individuals, and the psychosocial impact that may occur on victims of bullying. This article also discusses the role of the school environment, the role of teachers, as well as prevention and response strategies that can be implemented to create a safe and supportive learning environment for all students. By understanding the concept of bullying holistically, it is hoped that it can provide better insight in overcoming and preventing bullying behavior in elementary schools in order to realize inclusive and competitive education.